Effect of cap gap and welded seam strength on concrete-filled steel tube arch bridge ribs. (5th April 2023) - Lu, Zhengran; Guo, Chao
In this paper, the quantitative analysis is investigated for the concrete-filled steel tube (CFST) ribs strength that contained defects. The friction Coulomb model was used to investigate the interaction between the steel tube and the concrete core. Based on the non-destructive testing data, the finite element analysis is simulated with ABAQUS to obtain the strength of serviced concrete-filled steel tube ribs containing cap gaps and reduced spiral-welded seam strength which is exposed to weak eccentric axial compression. The results show that spiral-welded seam defects have weaker influence on the bearing capacity of CFST than that on empty steel tube. However, they have a significant influence on CFST local yield failure mode. The cap gap defects have effect on the shape of N - ε relationships. For CFSTs with composite defects, welded seam defects weakened local steel tube restrain capacity to concrete, resulting in CFST bending failure.